The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/14651858.cd006981.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for sialorrhea (excessive saliva) in people with motor neuron disease/amyotrophic lateral sclerosis

Abstract: There is some evidence for use of botulinum toxin injections to salivary glands for the treatment of sialorrhea in MND. Further research is required on this important symptom. Data are needed on the problem of sialorrhea in MND and its measurement, both by patient self report measures and objective tests. These will allow the development of better randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 35 publications
(4 reference statements)
0
36
0
2
Order By: Relevance
“…Side effects were reported in 54% of such patients, a rate similar to that seen overall with anticholinergics. The switching and combination of anticholinergics was common place in this study, but is not well discussed in the literature and deserves further exploration [3,6,19]. It would also be useful to identify the common factors in patients who do not respond well or are intolerant to anticholinergics.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Side effects were reported in 54% of such patients, a rate similar to that seen overall with anticholinergics. The switching and combination of anticholinergics was common place in this study, but is not well discussed in the literature and deserves further exploration [3,6,19]. It would also be useful to identify the common factors in patients who do not respond well or are intolerant to anticholinergics.…”
Section: Discussionmentioning
confidence: 89%
“…Despite remaining relatively unaddressed in many reviews and guideline articles [3,6,5,19], the use of conservative measures was often reported as part of the management for both thick and thin secretions. These are largely simple interventions which can be considered at the early stages of a secretion problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This significant efficacy was obtained by a non-invasive treatment and a method of administration that thanks to ultra-sound guidance minimizes the risk of iatrogenic injuries, as the loss of the facial nerve [21].…”
Section: Discussionmentioning
confidence: 99%
“…In some instances, additional measures to reduce secretions are worth attempting, such as scopolamine patches 64 or parotid gland injection with botulinum toxin. 65 Once patients start to tolerate SBTs, a one way speaking valve 66 can be used to allow phonation over the vocal cords and also enhance swallowing by augmenting subglottic pressure. In patients who cannot wean from MV these devices can theoretically be used "in line" to allow speech in mechanically ventilated patients.…”
Section: Tracheostomy Tube Management During Pmvmentioning
confidence: 99%